Business Games in Training Engineering Students; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Khrushchev Yu. V. Yuri Vasilievich; Batseva N. L. Natalya Lenmirovna; Fix N. P. Natalia Pavlovna; Chesnokova I. A. Irina Anatolievna; Kharkovskaya V. V. Valeriya Vladimirovna (2015, 2015)
Title screen